Peoples of the Enemy? Ukrainians and Russians 1995–2011. Issue 4 (December 2016) - Grogan, Louise
Abstract This paper tests three hypotheses about the origins of the conflict which began in 2014 in Ukraine, using the 1995–2011 World Values Surveys. First, a hypothesis that the economic situation of young fighting-age men in Eastern Ukraine worsened relative to that of young men in Russia during 1995–2011 is examined. Second, a hypothesis that the political views of respondents in Eastern Ukraine became more like those of people in neighbouring Russian regions is investigated. Third, a hypothesis that people in Eastern Ukraine became relatively more disillusioned with the quality of their national institutions during this period is tested. None of these three hypotheses is much supported by the data.